Highly processible and electrochemically active graphene-doped polyacrylic acid/polyaniline allowing the preparation of defect-free thin films for solid-state supercapacitors. Issue 77 (22nd August 2015) - Wang, Yongguang; Wang, Xiangyu; Tang, Shaochun; Vongehr, Sascha; Ali Syed, Junaid; Meng, Xiangkang
<x xml:space="preserve">Abstract</x> Graphene doped polyacrylic acid/polyaniline composites were prepared with excellent processibility for ensuring ultrathin, defect-free and highly flexible films as well as high electrochemical performance.